English Students' Perception toward the Use of Youtube in Improving Students' Pronounciation - Daulay, Ernita; Mu'adzah Rana, Nuha (ENGLISH FRANCA : Academic Journal of English Language and Education, 2024)
This research aims to explore English students' views regarding the usage of social media platforms like YouTube, specifically the "The Wizardliz" channel, in enhancing students' pronunciation. This study seeks to investigate students' perceptions of using YouTube videos to improve English language learning and to determine if YouTube videos can be utilized to enhance English pronunciation. The study employs a qualitative descriptive method, sampling students of English education at a public university, using questionnaires and interview instruments. Data collection is conducted through questionnaires. Qualitative data analysis is used in this research. The results indicate that students' views of using YouTube videos, particularly the "The Wizardliz" channel, to enhance pronunciation are highly effective. The questionnaire results, consisting of 11 items, show that the average views score of students is 50% in the "Strongly Agree" category and 49.93% in the "Agree" category. Based on these findings, YouTube videos can be considered a productive and effective medium beneficial for improving English pronunciation.Â